Do recent meteorological drought events in central Italy result from long‐term trend or increasing variability?. (14th December 2021) - Romano, Emanuele; Petrangeli, Anna Bruna; Salerno, Franco; Guyennon, Nicolas
Abstract: The Mediterranean area is one of the most important "hotspot" where the effects of climate change are more evident, with an increase of extreme events such as hot waves and intense droughts. From this perspective, central Italy, which in the recent past suffered from the impact of intense negative anomalies of precipitation on water resources, shows peculiar characteristics, being its meteoclimatic regime determined by global, regional and local factors. In this context, this study aims at exploring the variability in time and space of the precipitation regime in central Italy over the period 1960–2020 analysing global factors, represented by indexes of teleconnection, and local factors such as orography and distance to the sea. Findings indicate an increase of drought events during the last 20 years, in a general pattern characterized by stationary precipitation amounts. This trend is clearer on the Tyrrhenian coast with a number of months under severe drought conditions increasing from 5% (1965–1999) to 24% (2000–2020). The strengthening of the periodic signal of precipitation is related mainly to the Atlantic Multidecadal Oscillation Index and the Western Mediterranean Oscillation Index. Considering the relationship between precipitation and teleconnection patterns over short time scales (few months), correlations are stronger with the North Atlantic Oscillation index and in general with the Atlantic patterns rather than with the Artic patterns, especially for the Adriatic side. Abstract : This study aims at exploring the variability in time and space of the precipitation regime in central Italy (1960–2020) analysing global factors, represented by indexes of teleconnection, and local factors such as orography and distance to the sea. Findings indicate an increase of drought events during the last 20 years, in a general pattern characterized by stationary precipitation amounts. The strengthening of the periodic signal of precipitation is related mainly to the Atlantic Multidecal Oscillation Index and the Western Mediterranean Oscillation Index.